The boundary currents at 24ºS : the Barzil and the Benguela Currents, and the nadw in the deep western and eastern boundaries - Santana Toscano, Daniel (2019)
The Brazil and Benguela Currents and the North Atlantic Deep Water flow in the Atlantic Ocean at 24°S in 2009 are studied by the implementation of an inverse model with GO-SHIP hydrographic data. Additionally, the net meridional transports of mass, heat and freshwater are calculated. The Brazil Current flows over the westernmost stations with a mass transport of -3.3±1.0 Sv to the south. Meanwhile, the Benguela Current System flows northward with a transport of 13.2±3.3 Sv. The Deep Western Boundary Current drives the North Atlantic Deep Water from the north to the south of the Atlantic Ocean, where it splits into two branches. One of them flows through the western boundary and the other flows from the middle of the South Atlantic Ocean to its eastern boundary, the net transport of the NADW is -25.5±1.3 Sv. The heat transport shows a northward flux of 1.0±0.1 PW, higher than previous studies. The freshwater budget showcases a -0.8±0.2 Sv transport from the ocean to the atmosphere (evaporation), matching the results of previous studies.